2000
DOI: 10.1086/300145
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Human Homosexual Behavior

Abstract: Homosexuality presents a paradox for evolutionists who explore the adaptedness of human behavior. If adaptedness is measured by reproductive success and if homosexual behavior is nonreproductive, how has it come about? Three adaptationist hypotheses are reviewed here and compared with the anthropological literature. There is little evidence that lineages gain reproductive advantage through offspring care provided by homosexual members. Therefore, there is little support for the hypothesis that homosexuality ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
1
13

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 88 publications
2
64
1
13
Order By: Relevance
“…Sexual orientation is commonly understood as patterned sexual desire that may lead to sexual behavior with members of one or the other sex. However, consonant with the functional explanations to be discussed below, much, if not most, same-sex sexual behavior occurs in those who do not identify as exclusively homosexual in orientation (Diamond & Wallen, 2011;Kinsey, Pomeroy, & Martin, 1948;Kirkpatrick, 2000). Our theoretical focus here is on a broad category of behavior, that which is erotic and occurs with members of the same sex, and its hormonal and motivational underpinnings (which include, but are not limited to, sexual desire); we consider sexual orientation or identity only secondarily, as this is not isomorphic with behavior.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…Sexual orientation is commonly understood as patterned sexual desire that may lead to sexual behavior with members of one or the other sex. However, consonant with the functional explanations to be discussed below, much, if not most, same-sex sexual behavior occurs in those who do not identify as exclusively homosexual in orientation (Diamond & Wallen, 2011;Kinsey, Pomeroy, & Martin, 1948;Kirkpatrick, 2000). Our theoretical focus here is on a broad category of behavior, that which is erotic and occurs with members of the same sex, and its hormonal and motivational underpinnings (which include, but are not limited to, sexual desire); we consider sexual orientation or identity only secondarily, as this is not isomorphic with behavior.…”
Section: Introductionmentioning
confidence: 74%
“…Many individuals appear capable of sexual arousal toward members of the same sex under the right circumstances (e.g., during adolescence; in initiation rites, see Muscarella, 2006), and the ethnographic record indicates that same-sex sexual behavior is found in a majority of societies, spanning a wide range of social complexity, and at times occurring at fairly high frequencies (Kirkpatrick, 2000;Muscarella, 2007;Ross & Wells, 2000; see also Rind & Yuill, 2012). In laboratory studies, self-identified heterosexual women, on average, have been shown to have a generalized genital response to both sexes, while heterosexual men have been shown to have a modest genital response to male sexual stimuli (e.g., Chivers, Rieger, Latty, & Bailey, 2004;Chivers, Seto, Lalumiere, Laan, & Grimbos, 2010;Rieger, Chivers, & Bailey, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wat vir ons seker is, is dat homoseksualiteit deel van seksuele diversiteit is. Daar is interessante (en selfs oortuigende) evolusionistiese uiteensettings van hoe homoseksuele gedrag deel geword het van die menslike spesie se oorlewing (Buss 1998;Kirkpatrick 2000). Sulke teorieë versterk die insig dat homoseksualiteit deel van menswees is.…”
Section: Homofobie En Heteroseksismeunclassified